Semaglutide for the treatment of obesity - Oleszczuk, Rafał; Kozińska, Iga; Gras-Ozimek, Jordi; Kozińska, Urszula; Oleszczuk, Anna (Journal of Education, Health and Sport, 2022)
Introduction and purpose Due to the growing tendency to diagnose obesity in patients, scientists are trying to find drugs that facilitate weight reduction. An example of such a formulation is the GLP-1 analogue semaglutide. The following article is an analysis of the current knowledge on the effectiveness and safety of obesity treatment with semaglutide based on available publications in Pubmed and Google Scholar databases. State of knowledge The main mechanism of semaglutide is based on a stimulation of insulin secretion from pancreatic beta cells, and inhibition of glucagon from alpha cells, inhibition of hepatic gluconeogenesis, and reduction of energy consumption with minimal impact on energy expenditure. In clinical trials, it showed the best results compared to placebo and other drugs used in weight reduction. Participants treated with semaglutide achieved a reduction in waist circumference, improvements in blood pressure parameters, HbA1c levels, total cholesterol, LDL cholesterol, triglycerides, and CRP protein, and increased HDL cholesterol levels. Semaglutide is well tolerated by patients, and its main side effects come from the gastrointestinal tract, including nausea, emesis, diarrhea. Summary The analysis of the latest publications and meta-analyzes of the literature shows that the use of semaglutide is safe and effective in the treatment of obesity. The positive effect of semaglutide on weight reduction also contributes to the reduction of the risk of cardiovascular events and other obesity-related complications. It is also well tolerated by patients, which translates into possible longer use, and weekly subcutaneous injections are not burdensome for patients. Key words: semaglutide; obesity; GLP-1 analogue; overweight